تقييم لأنماط انحصار الأرحاء الثالثة في المنطقة الجنوبية من سوريا - أبو عسلي, إياد (Latakia University Journal -Medical Sciences Series, 2019)
تهدف هذه الدراسة لتقييم نماذج انحصار الرحى الثالثة عند عينة مختارة من منطقة درعا. اشتملت العينة على 980 مريضاً راجعوا عيادات كلية طب الأسنان في الجامعة الدولية للعلوم والتكنولوجيا الخاصة تراوحت أعمارهم مابين 20-60 سنة. اختير من هذه المجموعة عينة من 519 مريضاً لدراسة توزع الأرحاء المنحصرة ومستوى بزوغها وتزويها, قسمت وفق الجنس إلى (218 ذكوراً) و(251 أنثى). أظهرت نتائج الدراسة أن 235 فرداً ( 54.28 % ) من مجمل عينة الدراسة يعانون من وجود حالة انحصار في الأرحاء الثالثة بواحدة منهم على الأقل, ولم يظهر الجنس علاقة ذات قيمة إحصائية لتوزع حالة الانحصار 49.787 % ذكوراً(117) و 50.213 % (118) إناثاً. كانت نسبة وجود الأرحاء المنحصرة في الفك السفلي اكبر بـ 1.64 مرة منه في الفك العلوي. التزوي الأكثر تواجداً للأرحاء المنحصرة في الفك السفلي كان بالاتجاه الأنسي 33.4 %, التزوي الأكثر شيوعا للأرحاء المنحصرة في الفك العلوي كان بالاتجاه العمودي بنسبة 49.6 %. المستوى B من الانحصار كان الأكثر شيوعاً في الفك العلوي (48.2 %) وكذلك في الفك السفلي (67.7 %). إن نمط الانحصار في الأرحاء الثالثة في المنطقة الجنوبية من سوريا تركز في الأرحاء السفلية وبدون وجود علاقة تربطه مع عامل الجنس The aim of this study is to evaluate the current patterns of the third molar impactions in a selected sample in Daraa. The sample collected from 980 patients who have attended Faculty of Dentistry clinics at the International University for Science and Technology, as age groups between 20 to 60 years old. Only 519 patients were accepted to determine the frequency of impacted third molars, their levels of eruption, and their angulations, divided according to gender to 218 males and 251 females, who were evaluated. The result of this study shows that 235 individuals (54.28%) show at least one impacted third molar, with no significant difference between males (117; 49.787%) and females (118; 50.213 %). The impacted third molars were 1.64 times more likely to occur in the mandible than in the maxilla. The most common angulations of impaction in the mandible was the mesial (33.4%), while the most common angulations in the maxilla, was the vertical (49.6%). Level B impaction was the most common in both maxilla (48.2%) and mandible (67.7%). The pattern of third molar impaction in the southern region of Syria is characterized by a high prevalence of impaction that is greater in the mandibles irrespective of the patient's sex.